Assessment of soil and water conservation management interventions on agricultural sustainability: A case study in Karma micro-watershed of West Bengal, India - KOIRI, HARISANKAR; PATRA, SANMAY KUMAR; RAY, RATNESWAR; PODDAR, RATNESWAR (Journal of Soil and Water Conservation, 2025)
Subsistence farming in the Karma micro-watershed of the Purulia district in West Bengal, India, is largely caused by the undulating topography, severe land degradation, low and irregular rainfall, acute water shortages, and the poor socioeconomic conditions of the farmers. A survey of farmers’ households using a random sample technique was conducted during 2017-18 to evaluate the impact of the soil and water conservation strategies on the transformation of developmental indices in agricultural production scenario before and after the implementation of integrated watershed management programme (IWMP). The results showed a distinct shift in the cropping pattern with the inclusion of high yielding cultivars; an increase in cropping intensity (13.38%); crop production, particularly for aman paddy (35.68%) and black gram (58.4%); and crop productivity, mainly of aman paddy (73.4%) and mustard (77.42%). These changes were specifically due to farmers’ households’ low to medium levels of knowledge acquisition (21.21 to 52.9%) and technology adoption (24.22 to 41.68%). There was a discrepancy between knowledge gain and knowledge diffusion in agricultural operation. A liaison among the government, NGOs, farmers, and other stakeholders as well as seasonal crop-specific training programme schedules, regular monitoring, the mobilization of subsidized input resources, and soft bank loan are therefore needed to strengthen the capacity building of the beneficiary farmers to implement the IWMP activities to the desired level for rehabilitating the soil and water resources and sustaining the agricultural productivity.